Catch-up and Convergence: Mechanism Design for Economic Development - Gottinger, Hans W. (Archives of Business Research, 2021)
A globalization process can be conceived as an evolving distributed algorithmic mechanism design (DAMD) that induces technology racing with natural catch-up processes of regional or country-wide competition. We describe the architecture of DAMD as the basis for development economics that lead to natural ongoing shifts in industrial performance and catch-up development. The link between implementation of DAMD and a dynamic system of country-wide industrial evolution is essential for understanding the diverse pattern of inter-country or inter-regional competition. By selectively reviewing a cross section of the catch-up literature on economic growth it is shown which essential elements of long-run sustainable growth dominate to achieve superior performance and why informationally efficient mechanism design of the Hayek-Hurwicz type is a superior vehicle for industry based economic growth in a globalized economy.